2009
DOI: 10.1038/eye.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sight impairment: a 10-year picture

Abstract: Introduction Registering a child as visually impaired is a potentially traumatic, but necessary, milestone in paediatric ophthalmology. Registration enables the provision of services essential to maximise the child's potential. Purpose This study was carried out to investigate the changes over a 10-year period in the rates of registration of childhood blindness at a tertiary paediatric ophthalmology department. Particular attention was given to diagnosis, whether the disease was preventable, time to registrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 13 publications
4
24
0
1
Order By: Relevance
“…In the United Kingdom Rahi and colleauges 9 referred to the most affected anatomic regions as the central nervous system, retina, and optic nerve. Durnian and colleagues 25 confirmed this finding.…”
Section: Discussionsupporting
confidence: 55%
“…In the United Kingdom Rahi and colleauges 9 referred to the most affected anatomic regions as the central nervous system, retina, and optic nerve. Durnian and colleagues 25 confirmed this finding.…”
Section: Discussionsupporting
confidence: 55%
“…Cerebral visual impairment may have increased simply through better understanding and recognition of the condition or there may be a true increase due to the improved survival of extremely premature infants who are more vulnerable to cerebral visual loss 2. In the developed world, cerebral visual impairment is the commonest cause of blindness 1 2 11. Contemporary estimates from the Oxford register in England found that cerebral visual impairment is a cause of visual impairment in up to 51% of cases, increasing to 87% for severe visual impariment 12.…”
Section: Discussionmentioning
confidence: 99%
“…Social deprivation has been linked to a variety of eye conditions,712 and the association between socioeconomic status and visual impairment is well known 13. In this study, we examined the link between social deprivation and nAMD in a population attending a university hospital in Birmingham, UK.…”
Section: Discussionmentioning
confidence: 99%
“…Social deprivation has also been linked to a number of ocular conditions, such as primary angle closure glaucoma,7 diabetic retinopathy,8 retinal detachment9 and late presentation of primary open-angle glaucoma (POAG) 10. It has also been found to be associated with worse visual acuity (VA) at presentation for cataract surgery,11 and paediatric visual impairment registration 12…”
Section: Introductionmentioning
confidence: 99%